Forgotten effects model in the strategic analysis of media - Gil-Lafuente, Anna M.; Amiguet Molina, Luis; Torres Martínez, Agustin (Unidad Editorial UPTC, 2020)
The consumer's appreciation of a means of communication is the result of the aggregation and composition of certain subjective estimates, which are also different in each individual, about some qualities or characteristics that a particular medium is believed to have. One of the main objectives is to find, directly or indirectly, those elements that consumers, whether consciously or unconsciously, seek and want about a means of communication. The purpose is for companies to focus their investments and resources on enhancing those qualities expected by citizens. This can be achieved by implementing actions aimed at influencing the audience in their appreciation of the qualities of the media at different levels. Therefore, we intend to establish mechanisms of causality, through different combinations of cause-effect relationships between the actions or measures to reach the audience, and the characteristics of the media most valued by consumers. Key words: forgotten effects, media, strategic analysis. JEL Classification: C02, C65, D81. Received: 04/04/2019.  Accepted: 25/06/2020.  Published: 30/06/2020.